The effects of conducting pathways to ground on the growth of carbon nanotubes on carbon fibre substrates. (2016) - Lee, Geunsung; Yu, Woong-Ryeol; Youk, Ji Ho; Lee, Jinyong
Most research on the production of carbon nanotubes (CNTs) on specific substrates has been conducted in electrically insulated environments; i.e., the substrate was on an insulated surface. The effect of conducting pathways between the substrate and ground on the growth of CNTs has not been studied; however, this might significantly affect the growth of CNTs because charged nanoparticles are involved in the synthesis of CNTs. Here, we investigate the effect of conducting pathways to ground using carbon fibre (CF) substrates and floating-catalyst chemical vapour deposition (FCVD). Conducting pathways between the CF substrate and ground were formed using various materials with different electrical properties. The CF substrate was analysed morphologically and structurally, demonstrating that CNTs did not grow on the CF substrate if there were conducting pathways to ground. Electrostatic measurements and simulations were also carried out to gain insight into the effects of these conducting pathways on the growth processes.